Problem of the instantaneous sound frequency measurement - Edward OZIMEK; Lech JUGOWAR; Leon RUTKOWSKI (Archives of Acoustics)
This paper presents a method for the measurement of the so - called quasi-instantaneous frequency of acoustic signals, which is an approximation of the instantaneous frequency defined on the basis of theoretical considerations. It also describes a measurement system of the (T, f-V) type which was built for this purpose, at the output of which the instantaneous value of the voltage V is proportional to the value of the quasi - period T_q or the quasi - instantaneous frequency f_q of a signal fed to the input. This system permits continuous registration of variations of the quasi - instantaneous frequency in real time. The characteristics of the system (T, f-V) given here and also the oscillograms of chosen test signals (with prescribed modulating functions) and real signals (e.g. those occurring in rooms) indicate the wide possibilities of its use in practice.